Derek Walcott's early writing (1948-1962): a critical reading - Herbertson, G (2022)
This thesis offers a critical reading of the poetry and drama Derek Walcott composed between 1948 and 1962. It contends that Walcott’s positions on imitation, hybridity and mimicry were influenced by his reading at school and changed little as he aged, but that the narrative currently employed to conceptualise his artistic trajectory has distorted this continuity. Largely comprising imitations of Anglo-European texts produced in the context of a self-avowed apprenticeship, his early writing was celebrated for its maturity and virtuosity in the 1940s and ’50s. However, it was retrospectively denigrated by detractors at the University of the West Indies in the 1960s and ’70s who framed it as beholden to Europe. Walcott defended his poetics amidst this criticism, but when discussions of hybridity’s positive potential gained critical currency in the West from the 1980s onwards, this earlier defence was misunderstood as a shift towards embracing Africa by scholars who could no longer access his earliest work. This gave rise to the idea that he departed from an overreliance on European writing in the early 1970s and developed an increasingly hybrid aesthetic thereafter. That narrative was generalised in the 1990s to formulate a model for Caribbean literature, which was then employed to theorise more widely about the interrelationship between modernist and postcolonial literatures.